1999
DOI: 10.1002/(sici)1099-0682(199910)1999:10<1659::aid-ejic1659>3.3.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Staudinger Reaction: Experimental and Theoretical Studies on the Stabilization of cis-Phosphazides

Abstract: Keywords: Phosphorus / Iminophosphorane / Staudinger reaction / Heterocycles / Ab initio calculations The Staudinger-model reaction H 3 P (1) + HN 3 (2) Ǟ H 3 P=NH H 3 P=NH and N 2 . This decomposition can be effectively hampered by intramolecular donor-acceptor interactions as (5) + N 2 (6) has been investigated at the CCSD(T)/6-31G**// MP2(Full)/6-31G* level. Primary products formed in this shown by calculations on model compounds as well as by experiments. Thus the reaction of a methylene-σ 3 ,λ 3 -reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
1
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(49 citation statements)
references
References 0 publications
3
44
1
1
Order By: Relevance
“…4 More recently, computational studies have provided more insight into the whole process 5. In particular, combined experimental and theoretical studies by Grützmacher and co‐workers suggested that phosphazides can be significantly stabilized when the nitrogen atom in the α position to the phosphorus is coordinated intramolecularly to a Lewis acid 5b. This prompted us to investigate the reaction of azides with phosphine borane derivatives ortho ‐(R 2 P)C 6 H 4 (BR′ 2 ) that we have recently introduced as ambiphilic ligands for transition metals 6.…”
Section: Methodsmentioning
confidence: 99%
“…4 More recently, computational studies have provided more insight into the whole process 5. In particular, combined experimental and theoretical studies by Grützmacher and co‐workers suggested that phosphazides can be significantly stabilized when the nitrogen atom in the α position to the phosphorus is coordinated intramolecularly to a Lewis acid 5b. This prompted us to investigate the reaction of azides with phosphine borane derivatives ortho ‐(R 2 P)C 6 H 4 (BR′ 2 ) that we have recently introduced as ambiphilic ligands for transition metals 6.…”
Section: Methodsmentioning
confidence: 99%
“…[50,51] Most relevantly, the classical Staudinger reaction [52][53][54][55][56] between phosphines and azides is thought to involve a transition state that consists of a fourmembered ring. [57][58][59] By using 15 N-labeled azides, Bergman et al showed that the nitrogen atom that is directly bound to the organic fragment becomes the imido nitrogen that remains bound to the metal upon extrusion of dinitrogen, [22] which is a direct consequence of the metallacyclic transition state, as illustrated in Scheme 5. The fundamentally different electronic structures of the Ta and Zr complexes translate to significantly different mechanisms for dinitrogen extrusion in these two seemingly related complexes.…”
Section: Different Pathways For the Release Of Dinitrogenmentioning
confidence: 99%
“…The mechanism of the classical Staudinger reaction has been thoroughly investigated by various experimental [15] as well as computational methods, [16,17] and is known to proceed via several intermediates. [15a, 18] The first step involves a nucleophilic attack of the phosphorus atom of 6 onto the azide moiety of 5 to form the phosphazide intermediate I (Scheme 3).…”
Section: Staudinger Reactionmentioning
confidence: 99%